2020
DOI: 10.1259/bjro.20200037
|View full text |Cite
|
Sign up to set email alerts
|

Artificial intelligence in radiology: does it impact medical students preference for radiology as their future career?

Abstract: Objective: To test medical students’ perceptions of the impact of artificial intelligence (AI) on radiology and the influence of these perceptions on their choice of radiology as a lifetime career. Methods: A cross-sectional multicenter survey of medical students in Saudi Arabia was conducted in April 2019. Results: Of the 476 respondents, 34 considered radiology their first specialty choice, 26 considered it their second choice, and 65 considered it their third choice. Only 31% believed that AI would replace … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(57 citation statements)
references
References 20 publications
1
40
4
Order By: Relevance
“…Model 10 shows that students who have higher self-rated familiarity with AI tend to view the EAI-enabled HR management more positively (rejecting H5). This result contradicts a Saudi Arabian study of medical students (Bin Dahmash et al 2020 ), which found anxiety toward using AI was correlated with a higher self-perceived understanding of this technology. This divergence with the literature can be explained by the diversity of the surveyed population, of which there are 48 countries in 8 regions and many possible future professions.…”
Section: Resultscontrasting
confidence: 74%
See 1 more Smart Citation
“…Model 10 shows that students who have higher self-rated familiarity with AI tend to view the EAI-enabled HR management more positively (rejecting H5). This result contradicts a Saudi Arabian study of medical students (Bin Dahmash et al 2020 ), which found anxiety toward using AI was correlated with a higher self-perceived understanding of this technology. This divergence with the literature can be explained by the diversity of the surveyed population, of which there are 48 countries in 8 regions and many possible future professions.…”
Section: Resultscontrasting
confidence: 74%
“…These findings are concurrent with previous studies that have examined the relationship between biometric surveillance and employee trust in the workplace (Rosenblatt 2018 ; Marciano 2019 ; Mateescu and Nguyen 2019 ; Manohka 2020 ). Similarly, a Saudi Arabian study of medical students (Bin Dahmash et al 2020 ) has found anxiety toward using AI was correlated with a higher self-perceived understanding of this technology.…”
Section: Literature Reviewmentioning
confidence: 93%
“…Model 10 shows that students who rate themselves as more familiar with emotional AI tend to view the application of this technology in the workplace more positively. This result contradicts a Saudi Arabian study of medical students (Bin Dahmash et al, 2020), which found anxiety toward using AI was correlated with a higher self-perceived understanding of this technology. This divergence with the literature can be explained by the diversity of the surveyed population, of which there are 48 countries and 8 regions.…”
Section: Determinants Of the General Attitude Toward The Ai Managerscontrasting
confidence: 94%
“…On the other hand, while a survey of 484 responses of 19 UK universities medical students show that a majority of students (88%) will play an important role in healthcare yet, nearly half the respondents express their concern about job loss in radiology due to AI (Sit et al, 2020). However, overall, most medical students' population found students express interest and desire to receive more AI training in their degree (Bin Dahmash et al, 2020;Pinto dos Santos et al, 2019;Sit et al, 2020).…”
Section: Students' and Professional's Attitude Toward Aimentioning
confidence: 99%
“…Model 10 shows that students who rate themselves as more familiar with emotional AI tend to view the application of this technology in the workplace more positively. This result contradicts a Saudi Arabian study of medical students (Bin Dahmash et al, 2020), which found 32 anxiety toward using AI was correlated with a higher self-perceived understanding of this technology. This divergence with the literature can be explained by the diversity of the surveyed population, of which there are 48 countries and 8 regions.…”
Section: Determinants Of Self-familiarity With Aicontrasting
confidence: 87%